Emergency Abdominal Surgery in Patient with Liver Cirrhosis - JB Suharjo B Cahyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
The number of patients with cirrhosis who require surgery is increasing. Therefore, it can be expected that a growing number of patients with cirrhosis will undergo surgery. Patients with cirrhosis are at particularly at high risk for morbidity and mortality due to the stress of surgery and the effects of general anesthesia. The risk for morbidity and mortality are influenced by the type of surgery and the extent of liver dysfunction. In patient with cirrhosis who undergo emergent abdominal surgery the mortality rate may reach 50%. The Child-Pugh score is used to predict perioperative morbidity and mortality rates for patients undergoing intra-abdominal surgery. The mortality rate patient with Child Classification A was 10%, Child Classification B was 31% and Child Classification C was 76%. So, an approach to perioperative risk assessment, evaluation, and management of the cirrhosis patients who is a surgical candidate is very crucial. We reported a case of an elderly male patient with liver cirrhosis who would undergo emergent abdominal surgery. Keywords: liver cirrhosis, emergency surgery, child pugh classification